2021
DOI: 10.1038/s41598-021-00809-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of SARS-CoV-2 and influenza virus causes more severe and prolonged pneumonia in hamsters

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently a serious public health concern worldwide. Notably, co-infection with other pathogens may worsen the severity of COVID-19 symptoms and increase fatality. Here, we show that co-infection with influenza A virus (IAV) causes more severe body weight loss and more severe and prolonged pneumonia in SARS-CoV-2-infected hamsters. Each virus can efficiently spread in the lungs without interference by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 26 publications
12
55
0
Order By: Relevance
“…Within the 7 month period of our study, we detected only 5 cases of influenza and SARS-CoV-2 co-infection out of the 13,467 ILI/SARI cases tested, thus indicating a low prevalence of co-infections during the reporting period. We identified more influenza B viruses as compared to influenza A, which was associated with severe disease in in-vitro studies and animal models [ 36 , 37 ]. In our study, severity and complications of the disease and hospital admission were associated with extremes of age and existing co-morbidities of the patients rather than the infecting virus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 7 month period of our study, we detected only 5 cases of influenza and SARS-CoV-2 co-infection out of the 13,467 ILI/SARI cases tested, thus indicating a low prevalence of co-infections during the reporting period. We identified more influenza B viruses as compared to influenza A, which was associated with severe disease in in-vitro studies and animal models [ 36 , 37 ]. In our study, severity and complications of the disease and hospital admission were associated with extremes of age and existing co-morbidities of the patients rather than the infecting virus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vaccinated mice were not fully protected, signi cantly decreased viral loads in lung sections as well as mild or inconspicuous lung damage were detected without symptoms of either disease, indicating distinct longterm protection against coinfection. Moreover, previous studies have reported a signi cant elevation of cytokine or chemokine expression in IAV-and SARS-CoV-2-coinfected animals, which may have an intrinsic correlation with in ammatory diseases 12,14 . Immunization with AR-CoV/IAV was shown to contribute to the reduction in numerous proin ammatory cytokines post-coinfection (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Several recent studies were conducted to explore whether SARS-CoV-2 and in uenza virus coinfection leads to more serious diseases, and the results have suggested that in uenza virus infection e ciently facilitates SARS-CoV-2 entry into host cells, leading to prolonged pneumonia with more severe lung lesions than single infection [11][12][13] . Coinfection with SARS-CoV-2 and in uenza virus also causes more severe weight loss and a higher proportion of death in mammals [12][13][14][15] , likely resulting in a more serious threat especially during the u season 16 . Therefore, the development of a combined vaccine is urgently needed to reduce the risk of infection with both pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments revealed that coinfection exacerbates pneumonia. 35 A discussion of this topic in the future is necessary.…”
Section: Discussionmentioning
confidence: 99%